1989
DOI: 10.1111/j.1399-0039.1989.tb01684.x
|View full text |Cite
|
Sign up to set email alerts
|

Are HLA class II genes controlling susceptibility and resistance to Brazilian pemphigus foliaceus (fogo selvagem)?

Abstract: In order to investigate the possible association between Brazilian pemphigus foliaceus and HLA, we studied 48 patients and 74 matched controls, all Brazilian Caucasoids, for HLA-A,B,C; DR1 to DRw8 and DQw1 to DQw3. The frequencies of DR1, DR4 and B16 were significantly increased, while DR7 was significantly decreased among the patients. Furthermore DQw2, likewise the DR specificities associated with it - DR3 and DR7 - never occurred among the patients in the absence of the susceptibility markers DR1, DQw1 or D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 22 publications
4
39
0
Order By: Relevance
“…Positive and negative associations with several HLA-DR and HLA-DQ antigens and HLA-DRB1 and HLA-DQB1 alleles have been reported in white, admixed and Amerindian Brazilian populations. [2][3][4][5] Only two studies of non-Amerindian populations were performed (with 48 2 and 38 3 patients). The aim of the present study was to evaluate the associations between EPF and HLA-DRB1 alleles and genotypes in a large cohort of cases and controls, and to examine the allelic interactions, that is, the effect of susceptible (SU), protective (PR) and neutral (NE) alleles in different genotypic combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Positive and negative associations with several HLA-DR and HLA-DQ antigens and HLA-DRB1 and HLA-DQB1 alleles have been reported in white, admixed and Amerindian Brazilian populations. [2][3][4][5] Only two studies of non-Amerindian populations were performed (with 48 2 and 38 3 patients). The aim of the present study was to evaluate the associations between EPF and HLA-DRB1 alleles and genotypes in a large cohort of cases and controls, and to examine the allelic interactions, that is, the effect of susceptible (SU), protective (PR) and neutral (NE) alleles in different genotypic combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory signals produced by the PD-1/PD-L pathway are of crucial relevance to the mechanisms maintaining tolerance and to terminate immune response in peripheral tissues, thus limiting organ damage (Freeman et al, 2000;Latchman et al, 2001;). The causes of initiation and perpetuation of the auto-aggressive responses in pemphigus foliaceus patients are largely unknown, although there is consensus about the influence of both genetic and environmental factors on susceptibility to this condition (Eaton et al, 1998;Petzl-Erler and Santamaria, 1989). The pathogenic concepts include defects in the maintenance of peripheral immune tolerance towards potential autoantigens (Coyle and Gutierrez-Ramos, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…According to the polygenic model of disease susceptibility, the presence of any of the susceptibility alleles is neither sufficient nor required for the disease to occur. The strongest associations thus far described are those with HLA class II alleles, known since 1989 and well established (Petzl-Erler and Santamaria, 1989;Moraes et al, 1991;Pavoni et al, 2003;VMMS Roxo, personal communication). Other candidate genes have also been analyzed in pemphigus foliaceus association studies, including genes of several cytokines and cytokine receptors (IL1A,IL1B,IL1R,IL4,IL4R,IL6,IL10,TNF,LTA) (Pereira et al, 2004;Roxo et al, 2003), TP53 and BAX, whose products participate in apoptosis (Köhler and Petzl-Erler, 2006) and DSG1, which encodes desmoglein 1, the major autoantigen in pemphigus foliaceus (Petzl-Erler and Malheiros, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…32 In Caucasian Brazilians with FS, Petzl-Erler & Santamaría found a higher incidence of HLA-DR1 and -DR4 antigens. 30 In a study carried out by Moraes et al the HLA-DRB1*0102 allele was pointed out as a marker of susceptibility for FS in Brazilians, whereas the HLADQw2 antigen was associated with protection. 33 The HLA-DRB1*0404, -DRB1*1402 and -DRB1*1406 alleles were associated with FS in Indians from Terena and Xavante tribes.…”
Section: Pemphigusmentioning
confidence: 99%
“…29 An increased frequency of HLA-B16 antigen was seen in Caucasian Brazilians with FS. 30 As to the Class II HLA, the HLA-DRB1*04 and -DRB1*14 alleles are associated with PV, regardless of the ethnic profile of the sample studied. 28 In Caucasian Argentinians with PV, Glorio et al reported an increased frequency of HLA-DR3 and -DR4 antigens, of HLA-DRB1*0402, -DQB1*0302, -DRB1*1401 and -DQB1*0503 alleles.…”
Section: Pemphigusmentioning
confidence: 99%